PENGEMBANGAN MEDIA PEMBELAJARAN MENGENAI ORGAN JANTUNG MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Aryo Nur Utomo; Dinda Lutfiyah (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
Interactive learning media is currently in great demand and has been widely applied to deliver subject matter, but in the health sector, it is still very minimal. This final project was made to create interactive learning media, especially regarding learning in the health sector. The 3D interactive learning media application using Augmented Reality Technology based on Android is designed and developed using 3D software, namely Blender 2.91.2, and supporting software for Augmented Reality, namely Unity 2017. The development of this media produces multimedia applications in the form of 3D-based interactive learning media. . This 3D-based learning media is presented in a simulation of Learning Media regarding the Heart Surface, Cardiovascular System, and Handling of Attacks and Cardiac Arrest. Keywords: Augmented Reality, Blender , Unity, Learning, Heart, Android